THERAPEUTIC DWELLING: MENTAL REHABILITATION AND HEALING CENTER WITH BIOPHILIC DESIGN CONCEPT IN WEST JAKARTA - Cyntha Dinisara (Architecture Study Program, Department of Civil Engineering, Faculty of Engineering, Universitas Negeri Semarang, Indonesia, 2023)
Mental health is one of the most important issues in the world, including Indonesia. Indonesia is the second-ranked country with the highest total cases of mental disorders in Southeast Asia, which reached 9,162,886 (Estimates Global Health, 2017). According to Asia's Least and Most Stressful Cities (2017), the city of Jakarta is ranked 6th as the most stressful city in Indonesia. This mental health problem is triggered by a fast-paced lifestyle which makes it difficult for the people of Jakarta to adapt to one another so that people feel stressed or depressed. Unfortunately, society's paradigm of mental health disorders creates a stigma that can hinder the healing and recovery of sufferers. From a psychological point of view, environmental factors play an important role in the healing process for people with mental disorders. This is commonly referred to as a healing environment which is carried out by managing the relationship between nature, humans, and buildings that can support healing. The purpose of writing this design report is to plan a Mental Rehabilitation and Healing Center with a Biophilic Architecture approach in the City of Jakarta which is capable of providing therapy for sufferers of mental disorders with details including (1) planning and designing a Mental Rehabilitation and Healing Center that can accommodate therapy activities and healing with the Healing Environment method; (2) planning and designing a Mental Rehabilitation and Healing Center with a Biophilic Architecture Approach in the City of Jakarta. The method of discussion in this report uses descriptive methods, with factual data collection through literature studies, observational studies, analysis, and conclusions. Key Word: Mental Rehabilitation Center in West Jakarta City, Biophilic Architecture.